The effect of intellectual capital disclosure on cost of capital: Evidence from technology intensive firms in Indonesia - Sri Hernita Barus; Sylvia Veronica Siregar (Journal of Economics, Business, and Accountancy Ventura, 2014)
There has been an increasing interest in intellectual capital due to the shift from the economical aspect into knowledge and information management aspect. Currently, public firms in Indonesia are not required by accounting standards or law to disclose most of their intellectual capital. However, firms may voluntarily choose to disclose such information. This research aims to examine the level of voluntary intellectual capital disclosure and also the effect of intellectual capital disclosure in firm’s annual report on cost of equity and cost of debt. The sample used is technology- intensive industry listed firms year 2010. It shows that the level of intellectual capital disclosure in firm’s annual report is relatively still low with an average of 35.77%. It also shows that there is a negative effect between intellectual capital disclosure and cost of equity. However, intellectual capital disclosure does not have significant effect on cost of debt.